2008
DOI: 10.1007/s10557-008-6155-2
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Natural Antioxidants from Tomato Extract in Treated but Uncontrolled Hypertensive Patients

Abstract: Tomato extract when added to patients treated with low doses of ACE inhibition, calcium channel blockers or their combination with low dose diuretics, had a clinically significant effect-reduction of BP by more than 10 mmHg systolic and more than 5 mmHg diastolic pressure. No side-effects to treatment were recorded and the compliance with treatment was high. The significant correlation between systolic blood pressure values and level of lycopene suggest the possibility of cause-effect relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(95 citation statements)
references
References 27 publications
3
91
0
1
Order By: Relevance
“…Tomato extract supplementation was associated with a clinically significant reduction of systolic and diastolic BP in hypertensive patients [15]. Garlic extract has also been associated with reduced systolic BP in patients with hypertension [16].…”
Section: + Modelmentioning
confidence: 98%
See 1 more Smart Citation
“…Tomato extract supplementation was associated with a clinically significant reduction of systolic and diastolic BP in hypertensive patients [15]. Garlic extract has also been associated with reduced systolic BP in patients with hypertension [16].…”
Section: + Modelmentioning
confidence: 98%
“…Raw ingredients in gazpacho exert a potentially valuable functional activity. Adding tomato extract to the diet of moderate hypertensive subjects is associated with a clinically significant reduction of systolic and diastolic BP [15]. Supplementing the diet of patients with uncontrolled hypertension with aged garlic extract also reduces systolic BP [16].…”
Section: Introductionmentioning
confidence: 99%
“…Tomato and its products are important dietary sources of antioxidants such as α-tocopherol and the carotenoids beta-carotene, phytotene and phytofluene [9]. Fluted pumpkin extract had the highest vitamin E content (5.07±0.04mg/100ml), and vitamin E is considered the 'standard antioxidant' to which other compounds with antioxidant activities are compared, especially in terms of its biological activity and clinical relevance [10].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary sources include tomatoes, guava, pink grapefruit, watermelon, apricots and papaya in high concentrations [237][238][239][240][241] . Lycopene produces a significant reduction in BP, serum lipids and oxidative stress markers [237][238][239][240][241] . Paran et al [241] evaluated 30 subjects with Grade Ⅰ hypertension, age 40-65, taking no antihypertensive or anti-lipid medications treated with a tomato lycopene extract (10 mg lycopene) for eight weeks.…”
Section: Lycopenementioning
confidence: 99%
“…Englehard gave a tomato extract to 31 hypertensive subjects over 12 wk demonstrating a significant BP reduction of 10/4 mmHg [238] . Patients on various anti-hypertensive agents including ACEI, CCB and diuretics had a significant BP reduction of 5.4/3 mmHg over 6 wk when administered a standardized tomato extract [239] . Other studies have not shown changes in BP with lycopene [240] .…”
Section: Lycopenementioning
confidence: 99%